Junior High School Creativity in Solving Geometry Problems - Irma Widya Lisa; Hery Susanto; Abadyo Abadyo; Edy Bambang Irawan (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
This research aims to describe creativity students in solving geometry problems in Junior High School. This research is explorative-qualitative. The research subjects are 3 students of the grade VIII of Junior High School who has high, moderate and low ability. The subjects were chosen by purposive sampling. This research result show that students who has high, moderate, and low ability tend to be fluent in problem-solving but are not flexible and lack of novelty in solving geometry problems.